Strategi Guru PAI Dalam Memanfaatkan Teknologi Dan Media Pembelajaran Di Era Digtal - Yuyum Demaisha; Nur Aisyah Fadya; Gusmaneli . (CV.ITTC INDONESIA, 2026)
This study examines the strategies of Islamic Education (PAI) teachers in utilizing technology and digital learning media in the digital era. The main issues discussed include the types of digital media used in PAI learning, effective learning strategies, the role of teachers in digital environments, as well as the challenges and solutions faced by teachers. The purpose of this study is to analyze how teachers optimize technology to improve the quality of learning. This research uses a qualitative approach with a literature review method by analyzing various relevant scientific sources. The results show that the use of digital media such as e-learning platforms, interactive applications, and audiovisual content can enhance student engagement and understanding. Teachers play an important role as facilitators, motivators, and controllers of technology use. However, challenges such as limited digital competence, infrastructure constraints, and misuse of technology still exist. Therefore, continuous training, strengthening digital literacy, and effective supervision are needed as solutions to optimize technology-based learning in Islamic education.